Palmitoylation: A Fatty Regulator of Myocardial Electrophysiology - Essandoh, Kobina; Philippe, Julie M.; Jenkins, Paul M.; Brody, Matthew J. (Frontiers in Physiology, 2020)
Regulation of cardiac physiology is well known to occur through the action of kinases that reversibly phosphorylate ion channels, calcium handling machinery, and signaling effectors. However, it is becoming increasingly apparent that palmitoylation or S-acylation, the post-translational modification of cysteines with saturated fatty acids, plays instrumental roles in regulating the localization, activity, stability, sorting, and function of numerous proteins, including proteins known to have essential functions in cardiomyocytes. However, the impact of this modification on cardiac physiology requires further investigation. S-acylation is catalyzed by the zDHHC family of S-acyl transferases that localize to intracellular organelle membranes or the sarcolemma. Recent work has begun to uncover functions of S-acylation in the heart, particularly in the regulation of cardiac electrophysiology, including modification of the sodium-calcium exchanger, phospholemman and the cardiac sodium pump, as well as the voltage-gated sodium channel. Elucidating the regulatory functions of zDHHC enzymes in cardiomyocytes and determination of how S-acylation is altered in the diseased heart will shed light on how these modifications participate in cardiac pathogenesis and potentially identify novel targets for the treatment of cardiovascular disease. Indeed, proteins with critical signaling roles in the heart are also S-acylated, including receptors and G-proteins, yet the dynamics and functions of these modifications in myocardial physiology have not been interrogated. Here, we will review what is known about zDHHC enzymes and substrate S-acylation in myocardial physiology and highlight future areas of investigation that will uncover novel functions of S-acylation in cardiac homeostasis and pathophysiology.